Rancang Bangun Alat Pencetak Briket Dengan Sistem Hidrolik - Nafie, Andri; Jasron, Jahirwan Ut; Tobe, Adi Y. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2023)
Briquettes are an alternative energy source to replace dependence on fossil fuels such as kerosene. However, in the process of making briquettes, there are still obstacles. The printing process still uses traditional methods, and the existing briquette printing equipment is also not equipped with a hydraulic system and pressure gauge, so it requires more printing time. It cannot know how much pressure is applied during printing. A briquette printing machine equipped with a hydraulic system and pressure gauge is needed to simplify the briquette printing process and save energy. The purpose of designing this briquette printing machine is to produce a press machine design with a hydraulic system equipped with a pressure gauge. The design method used in this research is an experiment using the Shigley-Mitchell method. The results of the analysis of the maximum stress of the material for 150 kg pressure on the frame 2,565x107 N/m2, the press cylinder 1,932x106 N/m2, the upper press piston 8,830x102 N/m2, the lower plunger piston 2,392x107 N/m2, and the maximum stress for the loading pressure on the connecting lever 1,433x107 N/m2, the pressing lever 2,873x108 N/m2, the material yield strength value 6,204 x 108 N/m2.